six one foot rulers laid end to end reach how many inches?
6 inches
18 inches
71 inches
72 inches
39 answers
72 inches
when 9 is multiplied by a number, the result is 90. which equation fits this statement
x - 90 = 90
x ÷ 9 = 90
9 + x = 90
9x = 90
x - 90 = 90
x ÷ 9 = 90
9 + x = 90
9x = 90
9x = 90
what is 20% of 60
20% of 60 is 12.
which improper fraction is equivalent to 5 11/40
To convert a mixed number to an improper fraction, multiply the whole number by the denominator of the fraction and add the numerator.
For 5 11/40, the improper fraction equivalent is:
5 * 40 + 11 = 251/40
For 5 11/40, the improper fraction equivalent is:
5 * 40 + 11 = 251/40
solve x - 8 = 68
x = 60
x = 76
x =75
x =61
x = 60
x = 76
x =75
x =61
To solve the equation x - 8 = 68, we need to isolate the variable x.
Adding 8 to both sides of the equation, we get:
x - 8 + 8 = 68 + 8
x = 76
So, x = 76.
Adding 8 to both sides of the equation, we get:
x - 8 + 8 = 68 + 8
x = 76
So, x = 76.
what is 74% of 700
74% of 700 is calculated by first converting the percentage to a decimal and then multiplying it by the number.
74% = 0.74
0.74 * 700 = 518
So, 74% of 700 is 518.
74% = 0.74
0.74 * 700 = 518
So, 74% of 700 is 518.
4,426 x 8
4,426 multiplied by 8 equals 35,408.
194,600 ÷ 100
194,600 divided by 100 equals 1,946.
9 2/3 + 3 1/9 =
To add mixed numbers, first add the whole numbers, then add the fractions separately.
9 + 3 = 12
Next, add the fractions:
2/3 + 1/9
To add fractions with different denominators, find a common denominator. In this case, the least common multiple (LCM) of 3 and 9 is 9.
Converting 2/3 to have a denominator of 9:
(2/3) * (3/3) = 6/9
Now the fractions have a common denominator of 9:
6/9 + 1/9 = 7/9
Combining the whole numbers and the fractions, we have:
12 + 7/9
The final result is 12 7/9.
9 + 3 = 12
Next, add the fractions:
2/3 + 1/9
To add fractions with different denominators, find a common denominator. In this case, the least common multiple (LCM) of 3 and 9 is 9.
Converting 2/3 to have a denominator of 9:
(2/3) * (3/3) = 6/9
Now the fractions have a common denominator of 9:
6/9 + 1/9 = 7/9
Combining the whole numbers and the fractions, we have:
12 + 7/9
The final result is 12 7/9.
whats 25% of 36.92
To find 25% of 36.92, we can multiply 36.92 by 0.25 (which is the decimal equivalent of 25%).
36.92 * 0.25 = 9.23
So, 25% of 36.92 is 9.23.
36.92 * 0.25 = 9.23
So, 25% of 36.92 is 9.23.
whats 25% more than 36.92
To find 25% more than 36.92, we need to add 25% of 36.92 to the original value.
First, let's calculate 25% of 36.92:
36.92 * 0.25 = 9.23
Now, let's add this value to 36.92:
36.92 + 9.23 = 46.15
So, 25% more than 36.92 is 46.15.
First, let's calculate 25% of 36.92:
36.92 * 0.25 = 9.23
Now, let's add this value to 36.92:
36.92 + 9.23 = 46.15
So, 25% more than 36.92 is 46.15.
47 x 39
The product of 47 multiplied by 39 is 1,833.
13 is 20% of what number
To find the number that 13 is 20% of, we can divide 13 by 0.20 (which is the decimal equivalent of 20%).
13 ÷ 0.20 = 65
So, 13 is 20% of 65.
13 ÷ 0.20 = 65
So, 13 is 20% of 65.
13/2 =
When you divide 13 by 2, the result is 6.5.
simplify 5 (5b)
To simplify the expression 5(5b), we can multiply 5 and 5b together:
5 * 5b = 25b
So, the simplified form of 5(5b) is 25b.
5 * 5b = 25b
So, the simplified form of 5(5b) is 25b.
3 is what percent of 12
To find what percent 3 is of 12, we can divide 3 by 12 and multiply by 100.
(3/12) * 100 = 0.25 * 100 = 25
So, 3 is 25% of 12.
(3/12) * 100 = 0.25 * 100 = 25
So, 3 is 25% of 12.
0.071 + 0.034
0.071 + 0.034 equals 0.105.
-3+(-2)
-3 + (-2) equals -5.
the sum of two integers is 5. their difference is 3. what are the 2 integers
Let's assume one of the integers is x.
According to the given information, the other integer can be represented as (5 - x) since their sum is 5.
Their difference is given as 3, so we can set up the equation:
x - (5 - x) = 3
Simplifying the equation:
x - 5 + x = 3
Combining like terms:
2x - 5 = 3
Adding 5 to both sides:
2x = 8
Dividing both sides by 2:
x = 4
Now we can substitute x = 4 back into one of the expressions to find the other integer:
5 - x = 5 - 4 = 1
So, the two integers are 4 and 1.
According to the given information, the other integer can be represented as (5 - x) since their sum is 5.
Their difference is given as 3, so we can set up the equation:
x - (5 - x) = 3
Simplifying the equation:
x - 5 + x = 3
Combining like terms:
2x - 5 = 3
Adding 5 to both sides:
2x = 8
Dividing both sides by 2:
x = 4
Now we can substitute x = 4 back into one of the expressions to find the other integer:
5 - x = 5 - 4 = 1
So, the two integers are 4 and 1.
21 = 14 + 7x
To solve the equation 21 = 14 + 7x, we must isolate the variable x.
Subtracting 14 from both sides:
21 - 14 = 14 - 14 + 7x
7 = 7x
Finally, dividing both sides by 7:
7/7 = 7x/7
1 = x
Therefore, the solution to the equation is x = 1.
Subtracting 14 from both sides:
21 - 14 = 14 - 14 + 7x
7 = 7x
Finally, dividing both sides by 7:
7/7 = 7x/7
1 = x
Therefore, the solution to the equation is x = 1.